2018
DOI: 10.1101/479634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neuropeptide Galanin is required for homeostatic rebound sleep following increased neuronal activity

Abstract: Sleep pressure homeostatically increases during wake and dissipates during sleep, but the molecular signals and neuronal substrates that measure homeostatic sleep pressure remain poorly understood. We present a pharmacological assay in larval zebrafish that generates acute, short-term increases in wakefulness followed by sustained rebound sleep after washout. The intensity of global neuronal activity during drug-induced wakefulness predicted the amount of subsequent rebound sleep. Whole brain mapping with the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 80 publications
(59 reference statements)
1
22
0
Order By: Relevance
“…Though the function of this phenomenon remains almost completely unstudied, ENCORE-D suggests that the period dominated by waking SWA in response to rapid-acting antidepressants represents a physiologically meaningful step for the subacute consolidation of activity-induced synaptic changes, involving alterations in both protein synthesis and energy metabolism, resembling deep or local sleep. Notably, a recent study conducted in zebrafish demonstrates the homeostatic emergence of a sleeplike state immediately following acute administration of pharmacological agents that prominently increase neuronal activation (Reichert et al, 2019).…”
Section: Sleep and Rapid Antidepressant Effectsmentioning
confidence: 99%
“…Though the function of this phenomenon remains almost completely unstudied, ENCORE-D suggests that the period dominated by waking SWA in response to rapid-acting antidepressants represents a physiologically meaningful step for the subacute consolidation of activity-induced synaptic changes, involving alterations in both protein synthesis and energy metabolism, resembling deep or local sleep. Notably, a recent study conducted in zebrafish demonstrates the homeostatic emergence of a sleeplike state immediately following acute administration of pharmacological agents that prominently increase neuronal activation (Reichert et al, 2019).…”
Section: Sleep and Rapid Antidepressant Effectsmentioning
confidence: 99%
“…In contrast, epileptogenic drugs like the GABA-receptor antagonist PTZ induce electrophysiological and behavioral seizures ( Baraban et al, 2005 ), which are observed as dramatic rearrangements in zebrafish bout structure ( Figure 1—figure supplement 3D ). The bout structure of Aβ rev , Aβ short , and Aβ long injected fish was highly similar to WT behavior ( Figure 1—figure supplement 3D,E and Figure 1—video 1 ), and the high-frequency bouts (HFB) indicative of seizures ( Reichert et al, 2019 ) were only found in PTZ exposed fish but not Aβ injected larvae ( Figure 1—figure supplement 3D,E ). Together these experiments indicate that exposure to Aβ modulates normal sleep/wake behavior without inducing toxic states.…”
Section: Resultsmentioning
confidence: 75%
“…Finally, if the behavioral states induced by Aβ are bona fide sleep/wake states, we reasoned that known zebrafish sleep/wake regulatory neurons should be engaged. Galanin-expressing neurons of the preoptic area and hypothalamus are active and upregulate galanin transcription during zebrafish sleep ( Reichert et al, 2019 ). Similarly, ISH for galanin 4–6 hr post-injection of Aβ oligomers revealed that wake-promoting Aβ short slightly decreased (−6%, blinded counts), while sleep-promoting Aβ long slightly increased (+12%, blinded counts), the number of galanin -positive cells in the hypothalamus compared to Aβ rev injected larvae ( Figure 2F–G ).…”
Section: Resultsmentioning
confidence: 99%
“…The LPO hypothalamus is required for both NREM and REM sleep generation and NREM sleep homeostasis (Lu et al, 2002;Lu et al, 2000;Ma et al, 2019;McGinty and Sterman, 1968;Nauta, 1946;Reichert et al, 2019;Sherin et al, 1996;Szymusiak et al, 2007;Zhang et al, 2015). We explored how NMDA receptors on LPO neurons regulate sleep.…”
Section: Discussionmentioning
confidence: 99%
“…In this structure, GABA/peptidergic neurons, e.g. GABA/galanin neurons, contribute to NREM sleep induction and sleep homeostasis (Chung et al, 2017;Kroeger et al, 2018;Ma et al, 2019;Reichert et al, 2019;Sherin et al, 1996;Zhang et al, 2015). To stay asleep, and prevent insomnia, it seems reasonable to assume that these sleep-promoting neurons would have to stay "on".…”
Section: Introductionmentioning
confidence: 99%